Cirripedia of Madeira - Wirtz, Peter (2018)
We give a list of Cirripedia from Madeira Island and nearby deep water, based on specimens in the collection of the Museu Municipal do Funchal (Historia Natural) (MMF), records mentioned in the literature, and recent collections. Tesseropora atlantica Newman and Ross, 1976 is recorded from Madeira for the first time. The Megabalanus of Madeira is M. azoricus. There are 20 genera containing 27 species, of which 22 occur in depths less than 200 m. Of these shallow water species, eight are wide-ranging oceanic forms that attach to other organisms or to floating objects, leaving just 13 truly benthic shallow water barnacles. This low diversity is probably a consequence of the distance from the continental coasts and the small area of the available habitat. No endemic species have been found.